2023
DOI: 10.1186/s13068-022-02255-2
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic debranching is a key determinant of the xylan-degrading activity of family AA9 lytic polysaccharide monooxygenases

Abstract: Background Previous studies have revealed that some Auxiliary Activity family 9 (AA9) lytic polysaccharide monooxygenases (LPMOs) oxidize and degrade certain types of xylans when incubated with mixtures of xylan and cellulose. Here, we demonstrate that the xylanolytic activities of two xylan-active LPMOs, TtLPMO9E and TtLPMO9G from Thermothielavioides terrestris, strongly depend on the presence of xylan substitutions. Results Using mixtures of phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In particular, MtLPMO9G exhibited dual catalytic activities, degrading cellulose and xylan through oxidation and hydrolysis reactions, respectively. Most importantly, unlike reported AA9 LPMOs that catalyzed oxidative cleavage of glycosidic bonds in the xylan backbone in the presence of cellulose, 20,43,44 MtLPMO9G could able to independently hydrolyze xylan. Taken together, these discovered catalytic properties of LPMOs indicated that AA9 LPMOs from M. thermophila could attack cellulosic and hemicellulosic components of lignocellulosic biomass through multiple approaches, providing novel insights into how M. thermophila efficiently broke down the complex three-dimensional recalcitrant structure of lignocellulosic biomass.…”
Section: Transcriptomic Analysis Revealed Expression Profiles Of Lpmo...mentioning
confidence: 76%
See 3 more Smart Citations
“…In particular, MtLPMO9G exhibited dual catalytic activities, degrading cellulose and xylan through oxidation and hydrolysis reactions, respectively. Most importantly, unlike reported AA9 LPMOs that catalyzed oxidative cleavage of glycosidic bonds in the xylan backbone in the presence of cellulose, 20,43,44 MtLPMO9G could able to independently hydrolyze xylan. Taken together, these discovered catalytic properties of LPMOs indicated that AA9 LPMOs from M. thermophila could attack cellulosic and hemicellulosic components of lignocellulosic biomass through multiple approaches, providing novel insights into how M. thermophila efficiently broke down the complex three-dimensional recalcitrant structure of lignocellulosic biomass.…”
Section: Transcriptomic Analysis Revealed Expression Profiles Of Lpmo...mentioning
confidence: 76%
“…11,36,37 Specifically, AA9 LPMOs exhibit activity towards cellulose and hemicellulose with β-1,4-linked glucose backbone. 20 AA14 LPMOs are active on xylan coated cellulose fibrils. 38 AA16 LPMOs boost AA9 LPMOs activity for cellulose degradation.…”
Section: Transcriptomic Analysis Revealed Expression Profiles Of Lpmo...mentioning
confidence: 99%
See 2 more Smart Citations
“…The breakdown of polysaccharides is central to many biological processes and involves multiple enzymes, including lytic polysaccharide monooxygenases (LPMOs). These powerful monocopper enzymes are capable of oxidizing C–H bonds at the C1 and/or C4 carbon of glycosidic linkages in a broad range of polysaccharide substrates, including cellulose, chitin, various types of hemicelluloses, , and starch. , Recently, these enzymes have also been shown to play a role in microbial pathogenesis , and cellular development. …”
Section: Introductionmentioning
confidence: 99%